The Shifting Function of Mamak in the Implementation of Minangkabau Customs in the Community of Jorong Tigo Tumpuak Nagari Taluak Lintau Buo District - Hattami, Anggi Putri; Hambali, Hambali; Haryono, Haryono (FKIP - Universitas Riau, 2025)
This research is motivated by the diminishing role of mamak in Jorong Tigo Tumpuak. Mamak functions more as a father in his wife's family. The position and role of a mamak also began to change, for example in terms of the economy and education of his nephews, it should be the mamak who is responsible for the economy and education of his nephews, but now the role is taken more by the father. The findings in this study explain that the Shifting Functions of Mamak in the implementation of Minangkabau Customs the economic function is successful or unsuccessful economically the nephews remains the responsibility of the mamak and participates in guiding the nephews. The educational function of a mamak does not play much of a role in delivering the nephews to be able to go to school even to college. The religious function of the mamak's role as a guide to religious values has shifted due to busyness, and some of the responsibility has shifted to parents and teachers. The customary function of the mamak's understanding of customs has also declined, causing this important role not to be fulfilled properly.